2019
DOI: 10.1021/jacs.9b03661
|View full text |Cite
|
Sign up to set email alerts
|

Chloride Control of the Mechanism of Human Serum Ceruloplasmin (Cp) Catalysis

Abstract: Unraveling the mechanism of ceruloplasmin (Cp) is fundamentally important towards understanding the pathogenesis of metal-mediated diseases and metal neurotoxicity. Here we report that Cl−, the most abundant anion in blood plasma, is a key component of Cp catalysis. Based on detailed spectroscopic analyses, Cl− preferentially interacts with the partially reduced trinuclear Cu cluster (TNC) in Cp under physiological conditions and shifts the electron equilibrium distribution among the two redox active type 1 (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 40 publications
3
29
0
Order By: Relevance
“…DFT has been applied to the understanding the mechanism of Cl − activation of O 2 reduction in ceruloplasmin (section 3.2). 203 The calculations showed Cl − bridging between the T2 Cu and one T3 Cu (Fig. 12) and changing the ligand geometry around the T2 Cu, consistent with the authors' EPR measurements.…”
Section: Application To Mco Inhibitionsupporting
confidence: 84%
See 1 more Smart Citation
“…DFT has been applied to the understanding the mechanism of Cl − activation of O 2 reduction in ceruloplasmin (section 3.2). 203 The calculations showed Cl − bridging between the T2 Cu and one T3 Cu (Fig. 12) and changing the ligand geometry around the T2 Cu, consistent with the authors' EPR measurements.…”
Section: Application To Mco Inhibitionsupporting
confidence: 84%
“…165,194 Solomon et al recently reported that Cl − binds preferentially to the partially reduced TNC of a human ceruloplasmin under physiological NaCl concentrations and pH. 203 They also noted a 10-fold increase in the reaction rate for o-dianisidine oxidation in the presence of 100 mM NaCl (at pH 7), confirming that Cl − can enhance the catalytic activity of ceruloplasmin under certain conditions.…”
Section: Catalysis Science and Technology Mini Reviewmentioning
confidence: 92%
“… 11 Fully reduced Cp undergoes a similar pathway ( Figure S7 , bottom), and our previous studies showed that Cp requires a fully reduced TNC to achieve fast reaction with O 2 (∼10 6 M –1 s –1 ). 22 However, we have demonstrated in this work that partially reduced forms of Cp (3e – - or 4e – -reduced) are able to reduce O 2 by recruiting one extra electron from a nearby tyrosine residue. To achieve this rapid reaction, the first step likely involves a proton-coupled electron transfer (PCET) process from Tyr107 to the T2 Cu to generate the fully reduced TNC ( Figure S7 , top).…”
Section: Discussionmentioning
confidence: 65%
“…Recently we reported that chloride, the most abundant anion present in plasma (with a [Cl – ] ≈ 0.1 M), binds to the partially reduced TNC and shifts the electron equilibrium distribution between T1 Cu sites and the TNC in the Cp reduction process. 22 The Cl – -binding-induced reduction potential separation enables controlled formation of a series of partially reduced forms of Cp with well-defined electron distributions, as shown in Scheme 2 . The fully oxidized Cp is reduced stepwise following the order of decreasing reduction potentials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation